A fully automatic system for underway N2O measurements based on cavity ring-down spectroscopy. Issue 8 (21st June 2018) - Zhan, Liyang; Zhang, Jixia; Li, Yuhong; Wu, Man; Liu, Jian; Lin, Qi; Liqi, Chen
ABSTRACT: N2 O is one of the most important greenhouse and ozone-depleting gases and has been the source of considerable concern in recent years. The oceans account for 1/4 of the global N2 O emission budget; however, the oceanic N2 O source/sink characteristics are not well understood. To enhance the study of oceanic N2 O source/sink characteristics, our laboratory developed a fully automatic underway system for surface water N2 O concentration and atmospheric N2 O mole fraction measurements consisting of a cavity ring-down spectroscopy (CRDS) instrument and an upstream device. The developed device can be programmed to switch the CRDS measurements from the equilibrator headspace to the atmospheric sample and the reference gas sample. The surface water N2 O concentration is calculated from the equilibrium headspace N2 O mole fraction in the equilibrator. The response time of this equilibrator is 3.4 min, and the estimated precision of this method for surface water N2 O measurements is better than 0.5% (relative standard deviation, RSD), which is one order of magnitude better than that of traditional gas chromatographic methods and can be further optimised. Data are acquired every 20 s, and the calibration frequency requirement of this system is approximately 7–10 days. This labor-saving underway system is a powerful tool for high-precision and high-resolution measurements of atmospheric and oceanic N2 O and can significantly improve the study of the characteristics of oceanic N2 O sources/sinks and their response to climate change.